KEANEKARAGAMAN SERANGGA HAMA PADA LAHAN TANAMAN PADI (Oryza sativa L.) DENGAN DAN TANPA REFUGIA DI DESA BESUR LAMONGAN - Fiza Intan Nur Oktaviani; Fita Fitriatul Wahidah; Trisnan Alif (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
The used of refugia plants can be a solution in pest control by providing microhabitats for natural enemies. There are predators and parasitoids as alternative hosts. This study aimed to determine the diversity of insect pests in rice plantations using refugia and without refugia plants in Besur Village, Lamongan. This study used the rice variety Mentik Wangi Susu. The sampling method used 3 kinds of traps: sweep net, pit fall trap, and yellow sticky trap. The results showed that the insect pests found were 5 orders, 11 families, and 14 species with a total of 1272 individuals on refugia land and 1534 individuals on land without refugia. The Shanon-Weiner diversity index (H?) of insect pests on refugia land is H? = 1.93 and on land without refugia H? = 1.86 which is in the medium criteria. Keywords:Zea mays L., refugia, diversity, pest, insect